Beyond Religious Interpretations Islamic Fundamentalism and the Politics of Sexuality and Gender - Farid Muttaqin (Jurnal Peradaban, 2022)
Abstract This paper discusses the rising phenomenon of deploying sexuality and gender by Islamic fundamentalist groups in contemporary political situations. Rather than contextualizing the case as a form of patriarchal and heteronormative approaches in interpreting Islamic teachings, this article addresses a more systematic Islamic political agenda that roots in the history of sexuality in the Islamic context. This paper elaborates and traces the influential impacts of the construction and production of the discourse of marriage, homosexuality, controlling women’s body and sexuality, and the authority of male clerics (ulama) in Islamic knowledge and law production to the revival of contemporary politics of gender and sexuality among Islamic fundamentalist groups both in Indonesia and beyond. Examining current social and political dynamics, both in Indonesia and at global level, this article offers a new analytical frameworkbeyond academic interpretation (tafsir) in understanding the politics of gender and sexuality in the context of emerging Islamic fundamentalism.